The Role of Low-Intensity Biostimulation Laser Therapy in Transforming Growth Factor β1, Bone Alkaline Phosphatase and Osteocalcin Expression during Orthodontic Tooth Movement in Cavia porcellus - Narmada, Ida Bagus; Rubianto, Muhammad; Putra, Suhartono Taat (European Journal of Dentistry, 2019)
Objective The aim of this study is to analyze the low-intensity laser therapy (LILT) biostimulation mechanism as adjuvant therapy within orthodontic treatment as a means of accelerating bone remodeling by transforming growth factor β1 (TGF-β1), bone alkaline phosphatase (BALP), and osteocalcin (OSC) expression.Materials and Methods An analytical experimental method incorporating a posttest only randomized the control group design. The sample consisted of 24 3- to 4-month-old male Cavia porcellus weighing between 300 and 500 g divided into three groups (group 1: control, group 2: received orthodontic treatment, and group 3: received orthodontic treatment with irradiation LILT). LILT biostimulation at a dose of 4 joule/cm2 was performed daily for 3 min on the mesial-distal labial-palatal of the first dextra and sinistra incisor for 2 weeks. The TGF-β1, BALP, and OSC expression was subjected to immunohistochemical analysis. An analysis of variance with multiple comparison, a Tukey's honestly significant difference test, a Kruskal–Wallis test, and a Wilcoxon–Mann–Whitney test were all performed (p < 0.05).Results TGF-β1 expression was significantly different (p = 0.047; p < 0.05) in the tension area, but not in the compression side (p = 0.154; p > 0.05). BALP expression was significantly different in both the tension (p = 0.009) and compression areas (p = 0.005; p < 0.05). OSC expression was significantly different (p = 0.034; p < 0.05) in the tension side, but not in the compression area (p = 1.194; p > 0.05).Conclusion LILT biostimulation can increase TGF-β1, BALP, and OSC expression during orthodontic tooth movement.
Keywords: bone alkaline phosphatase; irradiation low-intensity laser therapy; orthodontic tooth movement; osteocalcin, transforming growth factor β1